Pregled konfliktov med medvedi in ljudmi - Krofel, Miha (Gozdarski vestnik, 2012)
Throughout the history people have always been coming into conflicts with bears and number of conflicts in Slovenia is increasing in recent years. Good understanding of causes for human-bear conflicts is the first step for their effective resolution. In this paper we present a review of the existing knowledge of human-bear conflicts and experiences with different conflict mitigation measures from Slovenia and other countries. Based on this review we prepared recommendations for future management of human-bear conflicts in Slovenia. Human-bear conflicts are very diverse and are mainly connected with bear's opportunistic foraging and consumption of food and with people's fear of bear attack on humans. Several factors affect probability of human-bear conflict and the most important is probably access to anthropogenic food (slaughter remains, garbage etc.). On the other hand, it seems that bear density is not significantly connected with number of conflicts. Much more important is the number of problematic bears. Although such bears represent only a small part of bear population, they usually cause majority of all human-bear conflicts, while majority of other bears get involved in conflict only rarely or never. Experiences from last decades worldwide indicate that one of the most effective conflict prevention measures is to prevent bears' access to anthropogenic food sources. In Slovenia very little attention has been given to this management measures so far. We prepared a list of priority conflict prevention measures that proved to be very effective in other countries and could considerably decrease number of conflicts in Slovenia. In addition to prevention of access to anthropogenic food, also removal of conflict bears is important short-term conflict resolution measure, given that such intervention doesn't threaten the bear population.
Keywords: rjavi medved; Ursus arctos; konflikti; velike zveri; upravljanje; management; Slovenia; Slovenija